2015
DOI: 10.3390/ijms16048789
|View full text |Cite
|
Sign up to set email alerts
|

Potential Natural Products for Alzheimer’s Disease: Targeted Search Using the Internal Ribosome Entry Site of Tau and Amyloid-β Precursor Protein

Abstract: Overexpression of the amyloid precursor protein (APP) and the hyperphosphorylation of the tau protein are vital in the understanding of the cause of Alzheimer’s disease (AD). As a consequence, regulation of the expression of both APP and tau proteins is one important approach in combating AD. The APP and tau proteins can be targeted at the levels of transcription, translation and protein structural integrity. This paper reports the utilization of a bi-cistronic vector containing either APP or tau internal ribo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 73 publications
1
8
0
Order By: Relevance
“…When the hidden platform is removed during the probe trial, the duration for the aging mice staying in the target quadrant provides a quantitative evaluation on the ability of spatial learning and memory. 67 In comparison with the CD group, a significant decrease of duration in the target region displayed by aging mice in the WD group supports the cognitive impairment that resulted from Western diet-induced metabolic syndrome ( Figure 5 f). Of importance, a daily treatment of DNIC-1 improves the cognitive impairment in aging mice with metabolic syndrome based on the increase of the duration in the target region featured by WD:NO group ( p = 0.217 in comparison with WD group).…”
Section: Results and Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…When the hidden platform is removed during the probe trial, the duration for the aging mice staying in the target quadrant provides a quantitative evaluation on the ability of spatial learning and memory. 67 In comparison with the CD group, a significant decrease of duration in the target region displayed by aging mice in the WD group supports the cognitive impairment that resulted from Western diet-induced metabolic syndrome ( Figure 5 f). Of importance, a daily treatment of DNIC-1 improves the cognitive impairment in aging mice with metabolic syndrome based on the increase of the duration in the target region featured by WD:NO group ( p = 0.217 in comparison with WD group).…”
Section: Results and Discussionsupporting
confidence: 54%
“…It depends on distal cues to crossing from start locations around the perimeter of an open swimming arena to locate a hidden escape platform. , During the acquisition phase of training (days 1–5 during week 17), all groups display a progressive decrease in latency to reach the hidden platform (Figure S16). When the hidden platform is removed during the probe trial, the duration for the aging mice staying in the target quadrant provides a quantitative evaluation on the ability of spatial learning and memory . In comparison with the CD group, a significant decrease of duration in the target region displayed by aging mice in the WD group supports the cognitive impairment that resulted from Western diet-induced metabolic syndrome (Figure f).…”
Section: Results and Discussionmentioning
confidence: 99%
“…A study demonstrated that fermented ginseng reversed memory impairment and reduced Aβ accumulation in the AD mouse model (50). Another study reported that NB34, a preparation of fermented Radix notoginseng , can serve in an alike functional manner to memantine, a drug used for the treatment of AD, by reducing the activities of both tau internal ribosome entry site and APP (51). …”
Section: The Effects Of Fermented Foods On Cognitive Functionmentioning
confidence: 99%
“…It is of interest to create multicistronic vector-based test systems for screening potential compounds for the treatment of neurodegenerative diseases. An example of such a test system is the human neuroblastoma cell line co-expressing APP and TAU genes separated by IRES and designed for the screening of AD therapy drugs [69,70]. Using the above test system, curcumin, its structural analogue demethoxycurcumin [69], and memantine (non-competitive NMDA receptor antagonist ( N -methyl- d -aspartate)) [70] have been able to inhibit APP and TAU IRES-dependent translation initiation.…”
Section: Multicistronic Vectors For Neurodegenerative Disease Therapymentioning
confidence: 99%